The Effect of Using Environmentally Friendly Materials and Energy Efficiency in the Production Process on Reducing Carbon Emissions in the West Java Automotive Industry - Farida Arinie Soelistianto; Tirangga Ansori; Andi Haslinah; Martono Dwi Atmadja; Bekti Utomo (West Science Interdisciplinary Studies, 2024)
This research quantitatively analyzes the effect of integrating environmentally friendly materials and energy-efficient production processes on reducing carbon emissions in the West Java automotive industry. Through surveys and statistical analysis, the study examines the adoption of sustainable practices among automotive manufacturers and assesses their impact on carbon emissions reduction. Findings indicate that companies actively embracing sustainable practices demonstrate a significant reduction in carbon emissions compared to those with minimal adoption. The results underscore the importance of prioritizing sustainability initiatives within the automotive industry to mitigate environmental impacts and contribute to global efforts to combat climate change.